METHODOLOGICAL FEATURES OF TEACHING PROFESSIONAL ENGLISH FOR FINANCE AND BANKING STUDENTS - Lysak, Halyna (The Modern Higher Education Review, 2025)
This paper examines the methodological features of teaching professionally oriented English for Specific Purposes (ESP) to students majoring in Finance and Banking within the context of Ukraine’s integration into the European and global educational space. The research aims to develop a differentiated ESP teaching model that aligns linguistic instruction with professional, cognitive, and intercultural requirements of the financial domain. Using a qualitative and comparative approach, the study analyses international and Ukrainian ESP methodologies and identifies specific linguistic, communicative, and analytical needs of finance and banking students. The findings reveal that effective ESP instruction in this field must integrate economic content, professional discourse, and intercultural competence while fostering analytical and reflective skills. The proposed differentiated model incorporates three interrelated dimensions (cognitive professional, communicative-interactive, and analytical reflective), ensuring professional relevance and adaptability across educational contexts. The study highlights the importance of interdisciplinary collaboration, authentic assessment, and digital learning tools in enhancing learner engagement and global employability.